Influenza virus decreases albumin uptake and megalin expression in alveolar epithelial cells - Alberro-Brage, Andrés; Kryvenko, Vitalii; Malainou, Christina; Günther, Stefan; Morty, Rory E.; Seeger, Werner; Herold, Susanne; Samakovlis, Christos; Vadász, István (Frontiers in Immunology, 2023)
Introduction Acute respiratory distress syndrome (ARDS) is a common complication of influenza virus (IV) infection. During ARDS, alveolar protein concentrations often reach 40-90% of plasma levels, causing severe impairment of gas exchange and promoting deleterious alveolar remodeling. Protein clearance from the alveolar space is at least in part facilitated by the multi-ligand receptor megalin through clathrin-mediated endocytosis. Methods To investigate whether IV infection impairs alveolar protein clearance, we examined albumin uptake and megalin expression in MLE-12 cells and alveolar epithelial cells (AEC) from murine precision-cut lung slices (PCLS) and in vivo, under IV infection conditions by flow cytometry and western blot. Transcriptional levels from AEC and broncho-alveolar lavage (BAL) cells were analyzed in an in-vivo mouse model by RNAseq. Results IV significantly downregulated albumin uptake, independently of activation of the TGF-β1/GSK3β axis that has been previously implicated in the regulation of megalin function. Decreased plasma membrane abundance, total protein levels, and mRNA expression of megalin were associated with this phenotype. In IV-infected mice, we identified a significant upregulation of matrix metalloproteinase (MMP)-14 in BAL fluid cells. Furthermore, the inhibition of this protease partially recovered total megalin levels and albumin uptake. Discussion Our results suggest that the previously described MMP-driven shedding mechanisms are potentially involved in downregulation of megalin cell surface abundance and clearance of excess alveolar protein. As lower alveolar edema protein concentrations are associated with better outcomes in respiratory failure, our findings highlight the therapeutic potential of a timely MMP inhibition in the treatment of IV-induced ARDS.